STUDI PEMBUATAN TABLET EFFERVESCENT DENGAN EKSTRAK BUNGA MAWAR MERAH (Rosa sp.) PADA PASCA POTONG BUNGA MAWAR DAN JENIS FILLER (NaHCO3, KHCO3, CaCO3) - Theovilla R. Rianty Dami (AGRICA, 2011)
Red roses (Rosa sp) are a decorative plant species. Their petals contain the pigment anthocyanin, which is classified as a flavonoid and is able to capture free radicals. Due to their popularity, roses are an abundant resource and can be processed into effervescent drink tablets. This study aims to investigate the influence of time after harvest and filler type on the quality of the red rose extract powder, on effervescent tablets made from the said extract and on effervescent drink quality. The study was conducted in two stages. Phase I tested the quality of pigment extract of hybrid varieties of Dutch roses. Three post-harvest durations were tested using a Randomized Block Design: fresh, or 0 days after harvesting (U0), 2 days after harvesting (U1) and 4 days after harvesting (U2). Phase II used a Randomized Block Design arranged in factorial to test rose extracts taken from flowers at 3 post-harvest durations (U0, U1, U2) in combination with 3 different filler types [NaHCO3 (N0), KHCO3 (N1), CaCO3 (N2)]. Resulting pigment extracts were analyzed for water quality, pigment quality, pH, and colour intensity. Effervescent tablets made from the various pigment extracts were also measured for water quality, sugar level, pH, moisture content, tablet density, and colour intensity. Study findings revealed that time after harvest affected pigment extract pH, absorbance, light (L), and red (a+)/yellow (b+) colour intensity, while water content and soluble solid content and quantity were unaffected. Analysis of effervescent tablets found that time after harvest, was linked to differences in water content, texture, light intensity (L) and red (a+)/yellow (b+) intensity while there was no effect on moisture level. Analysis of effervescent tablet drinks found that harvest time and filler type affected pH, dissolution speed, colour intensity and flavour. However, neither time after cutting nor filler type had a significant effect on the quantity of soluble solid, colour, appearance or taste of the drinks.